Dekolorisasi Malachite Green oleh Reagen Fenton: Optimalisasi Parameter dan Studi Kinetika - Said Ali Akbar (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2020)
The study of the decolorization of Malachite Green in solution using the Fenton reagent has been investigated. The effects of different reaction parameters such as hydrogen peroxide concentration, iron ion concentration, pH of the solution, and initial dye concentration have been carried out. In this study the experimental range for H2O2 concentrations varied from 0.2 mM to 4 mM and Fe2+ ions were 0.01-0.1 mM. All experiments were carried out at room temperature of 27 oC. Furthermore, the optimal oxidation condition with the concentration of MG dyes of 20 mg/L was with H2O2 0.5 mM, Fe2+ 0.05 mM, and pH at 3. The dye decolorization process of MG was also observed kinetically, it was found that the degradation process took place with first-order reaction rate. Under optimal conditions, the dye solution with a concentration of 20 mg/L completely decolorized within 60 minutes at 27ºC, and 76% of the Chemical Oxygen Demand (COD) was removed. This proves that MG was not only decolorized but also mineralized.